AB0254 Clinical utility of natural angiogenin antibodies in pediatric osteosarcoma patients. (23rd January 2014) - Savitskaya, Y.; Rico, G.; Linares, L.; Delgado, E.; Estrada, E.; Martinez, E.; Tellez, R.; Ibarra, C.
Abstract : Background: Children are most commonly diagnosed with osteosarcoma at 14 years. Early osteosarcoma detection is key to ensuring effective treatment. Tumour angiogenesis is one of the most important hallmarks of osteosarcoma, which enables its development, progression and metastasizing. The study of natural antibodies to tumor antigens has come to the attention of many researchers. Circulating markers found in the sera offer a minimally invasive method that can be used repeatedly over the course of treatment. Objectives: The aim of the study was to investigate if natural angiogenin antibodies (ANG-IgM) can be clinically useful for pediatric osteosarcoma patients. Methods: The study consisted of 87 patients (median age 14 years) with osteosarcoma and 87 healthy age matched counterparts. Serum ANG-IgM was analyzed by a novel ELISA in patients at time of diagnosis, during treatment and after therapy. Computed tomography angiography was performed in all the osteosarcoma patients. Results: We observed that before treatment serum ANG-IgM level in pediatric osteosarcoma patients was significantly higher (P<0.05) compared to that obtained in healthy children. During chemotherapy the value of ANG-IgM significantly decreased by 20-30%. After therapy we observed different serum level of ANG-IgM in patients with favorable and unfavorable prognosis. Serum ANG-IgM level was higher in patients with progression as compared to patients with remission of disease (P<0.01). Patients with poor prognosis had also higher serum level of ANG-IgM in comparison to patients with remission (P<0.01). Conclusions: Presented results suggest that ANG-IgM identify changes in tumour angiogenesis in pediatric osteosarcoma patients during anticancer therapy. These markers due to the non-invasive methods and their specificity might be useful in monitoring of clinical treatment of osteosarcoma patients. References: Poon RT: Clinical Implications of Circulating Angiogenic Factors in Cancer Patients. J Clin Oncol 2001, 19(4):1207-1225. Vollmers HP: Natural IgM Antibodies, the Ignored Weapons in Tumour Immunity. Histol Histopathol 2004, 19(3):897-905. Disclosure of Interest: Y. Savitskaya Grant/Research support from: FONSEC SSA/IMSS/ISSSTE/CONACyT SALUD-2010-C01, G. Rico: None Declared, L. Linares: None Declared, E. Delgado: None Declared, E. Estrada: None Declared, E. Martinez: None Declared, R. Tellez: None Declared, C. Ibarra: None Declared